Caries en el departamento del Tolima, basado en las investigaciones realizadas por la universidad Antonio Nariño sede Ibagué en los años 2015 A 2020 - Carrillo Melo, Juan Sebastián (Universidad Antonio Nariño, 2021)
Dental caries is one of the most prevalent diseases in the world (ENSAB 2014), currently there are few reports regarding the oral health situation in our community, it is necessary to carry out an epidemiological study, in order to know the magnitude of the problem of public health in the city of Ibagué and its surrounding municipalities. Descriptive cross-sectional research. With a documentary approach, for the search, compilation, analysis and interpretation of secondary data. For this research, there were 15-degree projects by dentistry students at the Antonio Nariño University in the city of Ibagué in the years between 2015 and 2020. The child population affected by caries was studied.